2018
DOI: 10.1002/2017gl076935
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Extreme Flood Levels by Impoundment Significantly Offset by Floodplain Loss Downstream of the Three Gorges Dam

Abstract: River flooding—the world's most significant natural hazard—is likely to increase under anthropogenic climate change. Most large rivers have been regulated by damming, but the extent to which these impoundments can mitigate extreme flooding remains uncertain. Here the catastrophic 2016 flood on the Changjiang River is first analyzed to assess the effects of both the Changjiang's reservoir cascade and the Three Gorges Dam (TGD), the world's largest hydraulic engineering project on downstream flood discharge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…This indicates that the USIC is possibly linked to the presence of dams in the Upper Yangtze basin, because these dams are usually operated in a similar manner to that of the TGD. The operation of the TGD can be synchronized with that of the upstream dams to play a greater role in flood control, drought relief, and electricity generation (Mei et al, ). However, negative effects of this synchronization are also increased, in particular, a reduction in the downstream discharge in autumn, during which the dams usually store water to fill the reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the USIC is possibly linked to the presence of dams in the Upper Yangtze basin, because these dams are usually operated in a similar manner to that of the TGD. The operation of the TGD can be synchronized with that of the upstream dams to play a greater role in flood control, drought relief, and electricity generation (Mei et al, ). However, negative effects of this synchronization are also increased, in particular, a reduction in the downstream discharge in autumn, during which the dams usually store water to fill the reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the upstream inflow change (USIC) of the TGD can result in alterations in the downstream flow regime, even if regulation effects of the TGD are discounted. Mei et al () reported that the dams located upstream the TGD attenuated the downstream flood peak that occurred on 25 July, 2016 by over 1.5 × 10 4 m 3 /s, which exceeds the contribution of the TGD (i.e., 1.45 × 10 4 m 3 /s). Therefore, the changes of the flow regime downstream the TGD should be attributed to the joint effects of the dam and the USIC.…”
Section: Introductionmentioning
confidence: 98%
“…Post-dam bank erosion is mainly caused by channel incision (Petts and Gurnell, 2005) and variations in the intra-annual flow regimessuch as the rapid drawdown in water levels in September and October during the recession stage of the TGD (Darby et al, 2002;Deng et al, 2018). Furthermore, climate changein particular the increased variability of the eastern Pacific El Niño under greenhouse warming (Cai et al, 2018)can increase the frequency of extreme rainfall in the Yangtze River basin, as is evident in the catastrophic floods of 2015 and 2016 (Li and Lu, 2017;Mei et al, 2018). In the post-dam period, given the lack of reduction in flood levels, frequent bank erosion and ongoing climate change, there is a continuing risk of flooding in the MYR despite the existence of the TGD.…”
Section: Impact Of Channel Change On Water Level and Flood Controlmentioning
confidence: 99%
“…Due to the complex nature of climate changes and of anthropogenic forcing (Allen & Ingram, 2002;Lu, 2004;Mei et al, 2018;Tang & Lettenmaier, 2012;Zhang et al, 2010Zhang et al, , 2011, the future variability of runoff is unpredictable. Due to the complex nature of climate changes and of anthropogenic forcing (Allen & Ingram, 2002;Lu, 2004;Mei et al, 2018;Tang & Lettenmaier, 2012;Zhang et al, 2010Zhang et al, , 2011, the future variability of runoff is unpredictable.…”
Section: Introductionmentioning
confidence: 99%